2023
DOI: 10.1111/1755-0998.13783
|View full text |Cite
|
Sign up to set email alerts
|

The promise and challenges of characterizing genome‐wide structural variants: A case study in a critically endangered parrot

Abstract: There is growing interest in the role of structural variants (SVs) as drivers of local adaptation and speciation. From a biodiversity genomics perspective, the characterization of genome‐wide SVs provides an exciting opportunity to complement single nucleotide polymorphisms (SNPs). However, little is known about the impacts of SV discovery and genotyping strategies on the characterization of genome‐wide SV diversity within and among populations. Here, we explore a near whole‐species resequence data set, and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 80 publications
0
25
1
Order By: Relevance
“…The integration of known genetic variation within the reference greatly facilitates mapping of reads that overlap such variants, thus improving both SV detection and genotyping, and reducing reference allele bias (Ameur, 2019). This approach has shown promising results for genome‐wide population‐scale SV detection in human ( Homo sapiens ; Yan et al., 2021), soybean ( Glycine max ; Lemay et al., 2022), lake whitefish ( Coregonus clupeaformis ; Mérot et al., 2023) and in kākāpō parrots ( Strigops habroptilus ; Wold et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of known genetic variation within the reference greatly facilitates mapping of reads that overlap such variants, thus improving both SV detection and genotyping, and reducing reference allele bias (Ameur, 2019). This approach has shown promising results for genome‐wide population‐scale SV detection in human ( Homo sapiens ; Yan et al., 2021), soybean ( Glycine max ; Lemay et al., 2022), lake whitefish ( Coregonus clupeaformis ; Mérot et al., 2023) and in kākāpō parrots ( Strigops habroptilus ; Wold et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, deleterious SVs may be overrepresented in small populations ( Wold et al 2021 ). As such, inquiries into the fitness effects of SVs ( Gaut et al 2018 ; Zhou et al 2019 ) and their relative contribution to mutational load are becoming increasingly important for applied conservation genomics ( Wold et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Part of the renewed interest in SVs and their identification is driven by advances in bioinformatic tools that facilitate the detection of SVs in sequencing data. However, considerable challenges still remain related to the incidence of false positives, which are known to far exceed the proportion of true positives—even for SVs discovered using short-read data at recommended (>20×) coverage ( Belyeu et al 2021 ; Wold et al 2023 ). For example, in a recent study on structural variation in 492 Atlantic salmon (resequenced at an average 8.1× coverage with Illumina short reads), Bertolotti et al (2020) reported that up to 91% of identified SVs were false positives after visual inspection with Samplot ( Belyeu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of known genetic variation within the reference greatly facilitates mapping of reads that overlap such variants, thus improving both SV detection and genotyping, and reducing reference allele bias (Ameur, 2019). This approach has shown promising results for genome-wide population-scale SV detection in human ( Homo sapiens ; Yan et al, 2021), soybean ( Glycine max ; Lemay et al, 2022), lake whitefish ( Coregonus clupeaformis ; Mérot et al, 2023) and in kākāpō parrots ( Strigops habroptilus ; Wold et al, 2023) .…”
Section: Introductionmentioning
confidence: 99%